The role of brand exposure and experience on brand recall—Product durables vis-à-vis FMCG. (March 2015) - Baumann, Chris; Hamin, Hamin; Chong, Amy
Abstract: The purpose of this study was to examine the role of brand exposure and experience on brand recall, mediated by three affectional drivers: brand trust, brand image and self-image congruence. The study distinguishes between an individual consumer׳s brand exposure and experience, and how these impact brand recall. Using original data collected from a survey of 219 consumers, brand recall models in two product categories (Fast Moving Consumer Goods FMCG and durable goods) were tested. Structural equation modelling (SEM) was applied, resulting in models for the two types of goods, establishing notable differences between durables and FMCGs. Experience influences brand recall in durable goods while brand recall is established via exposure for fast-moving consumer goods. This suggests that consumers are better able to recall durable goods brands if they have personally used them, while consumers of FMCG are more heavily influenced by advertising. Our study also established that brand trust has a significant role in mediating both of these relationships. Ultimately, the study establishes key differences between the brand recall of product categories, as well as the mediating role of brand trust, providing a framework for future brand recall research. Highlights: Brand recall modelled in 2 product categories: FMCG and durable goods. 3 affectional drivers mediate: brand trust, brand image and self-image congruence. Experience influences brand recall in durable goods. Brand recall established via exposure for fast-moving consumer goods. Recall for durable goods brands if personally used; FMCG influenced by advertising.